POTENSI PENGGUNAAN LIMESTONE SEBAGAI FILTER PADA KONSTRUKSI SANITARY LANDFILL - Ratna Yuniarti; Tri Sulistyowati (Purifikasi, 2006)
In general, a liner system in sanitary landfill consists of both geomembrane barrier and clay liner. Although geomembrane is an absolute barrier against advection, pollutants can permeate it by diffusion so that leakage may occur through the liner. Since clay liner can be damaged by leachate which has low or high pH, it is necessary to develop sanitary landfill by placing limestone as a filter between geomembrane and clay liner. Due to its common use in water treatment, limestone may increase the quality of leachate and provide protection for the clay liner. A series laboratory experimental study was carried out to investigate characteristics of limestone: natural water content, particle size, specific gravity, Atterberg limit and compaction. Hydraulic conductivity test of limestone with leachate as permeant is also conducted. Finally, the qualities of lindi before and after permeate into limestone are measured to determine the change in concentration of pollutants, and the effect of this filtration process on limestone’s chemical characteristics. Analysis showed the overall hydraulic conductivity of limestone to leachate is 1,86 x 10-6 cm/s. After permeating into limestone, the pH value of leachate reduced from 7,72 to 7,03. Pollutants in leachate decreased with regard to BOD from 390 mg/L to 260 mg/L and COD reduced by 33,33%. Due to its ability to remove pollutant in leachate, it is suggested to place limestone as a filter in sanitary landfill.